Adsorption equilibria of chlorinated organic solvents onto activated carbon - Yun, JH; Choi, DK; Kim, SH (AMER CHEMICAL SOC, 1998)
Adsorption equilibria of dichloromethane, 1,1,1-trichloroethane, and trichloroethylene on activated carbon were obtained by a static volumetric technique. Isotherms were measured for the pure vapors in the temperature range from 283 to 363 K and pressures up to 60 kPa for dichloromethane, 16 kPa for 1,1,1-trichloroethane, and 7 kPa for trichloroethylene, respectively. The Toth and Dubinin-Radushkevich equations were used to correlate experimental isotherms. Thermodynamic properties such as the isosteric heat of adsorption and the Henry's constant were calculated. It was found that the values of isosteric heat of adsorption were varied with surface loading. Also, the Henry's constant showed that the order of adsorption affinity is 1,1,1-trichloroethane, trichloroethylene, and dichloromethane. By employing the Dubinin-Radushkevich equation, the limiting volume of the adsorbed space, which equals micropore volume, was determined, and its value was found to be approximately independent of adsorbates.